2009
DOI: 10.1097/ijg.0b013e31819c46b1
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Oxidative Stress Induced by Intraocular Hypertension in Rats May be Ameliorated by Brimonidine Treatment and N-acetyl Cysteine Supplementation

Abstract: Brimonidine and NAC supplementation provide antioxidative properties to retina and decrease retinal damage induced by ocular hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 14 publications
0
28
0
2
Order By: Relevance
“…Moreno et al (2004) and Ozdemir et al (2009) showed that significant IOP elevation achieved by intraocular injection of hyaluronate is associated with reduced activity of retinal antioxidants such as SOD, CAT and glutathione peroxidase. Similar observations were made by Liu et al (2007) using RGCs in culture.…”
Section: Discussionmentioning
confidence: 98%
“…Moreno et al (2004) and Ozdemir et al (2009) showed that significant IOP elevation achieved by intraocular injection of hyaluronate is associated with reduced activity of retinal antioxidants such as SOD, CAT and glutathione peroxidase. Similar observations were made by Liu et al (2007) using RGCs in culture.…”
Section: Discussionmentioning
confidence: 98%
“…Even if glaucoma is a multifactorial disease [7,10], systemic oxidative stress may play an important role in the pathophysiology of POAG and PEG. Despite growing research on antioxidant therapy to prevent glaucoma, in both in vitro [64] and in vivo studies with animals [65] and humans [66], antioxidative supplementation has shown contradictory [66,67,68]. However, there were promising results of supplementation in endothelial function [69], some specific clinical conditions [70] and overall mortality [71].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NAC administered to a rat model of DR diminished the plasma markers of oxidative stress and inflammation (15-F(2t)-isoprostane and TNF-a, respectively), helping to minimize early events in DR (Tsai et al, 2009). Moreover, NAC supplementation to rats with induced ocular hypertension ameliorated the retinal oxidative damage through the maintenance of glutathione peroxidase and catalase levels, and the inhibition of retinal peroxidation (Ozdemir et al, 2009). NAC also prevented the increased expression of p53 and caspase 8, induced by long-term maintained hypoxia in bovine RPE primary cell cultures (Gerona et al, 2010), which makes it of great interest in oxygen stress-related diseases, such as AMD and other senescenceassociated pathologies.…”
Section: N-acetylcysteine (Nac)mentioning
confidence: 94%